2019
DOI: 10.1002/brb3.1475
|View full text |Cite
|
Sign up to set email alerts
|

Factors for cognitive impairment in adult epileptic patients

Abstract: ObjectiveTo analyze factors for cognitive impairment in epileptic patients.MethodsA total of 257 epileptic patients completed clinical memory scale (CMS) and 70 of them were further surveyed with mini‐mental state examination (MMSE), Montreal cognitive assessment (MoCA), digital symbol test (DSy), verbal fluency test, digit span test (DSp), Hamilton anxiety scale (HAMA) and Hamilton depression scale (HAMD). Monadic linear related analysis and multiple stepwise regression analysis were performed to evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 42 publications
8
44
0
1
Order By: Relevance
“…For example, 70% of control group reported having had seizures in the past 2 years, whereas 90% of intervention group reported seizures during the same period. Although the impact of seizure frequency on cognitive function is well known, 50 no difference was observed in baseline values between groups in all cognitive tests performed.…”
Section: Discussionmentioning
confidence: 82%
“…For example, 70% of control group reported having had seizures in the past 2 years, whereas 90% of intervention group reported seizures during the same period. Although the impact of seizure frequency on cognitive function is well known, 50 no difference was observed in baseline values between groups in all cognitive tests performed.…”
Section: Discussionmentioning
confidence: 82%
“…Due to the complexity of the disease, the previous studies assessing cognitive status using MoCA instrument and identifying variables associated with the prevalence of cognitive decline in different population of epilepsy patients also revealed varied results. Wang et al analyzed variables for cognitive decline in epilepsy patients using multiple linear regression analysis and showed that high level of education, good control of seizure, receiving monotherapy of AEDs, and absent of depression were protective variables against cognitive decline in these subjects 21 . Gavrilovic et al examined correlation between demographic and clinical characteristics and cognitive decline among drug-resistant and drugsensitive epilepsy patients in a cohort study and showed that duration of epilepsy, control of seizure, and EEG findings are significant predictors for cognitive decline in these subjects 34 .…”
Section: Discussionmentioning
confidence: 99%
“…The present study employed an unpaired categorical analytical case-control study, hence the sample calculation formula (n 1 =n 2 = {(Z α √2PQ + Z β √(P 1 Q 1 + P 2 Q 2 )):(P 1 -P 2 )} 2 ) was applied to determine the sample size. The lowest prevalence of cognitive impairment in epilepsy patients (P 2 ) was about 30% 21 . If α=0.05, Z α =1.96, β=0.2, Z β =0.84, P 2 =0.3, P 1 -P 2 =0.2, P=(P 1 + P 2 ):2, and Q=1 -P, the sample size required for each group was about 93 using the sample calculation formula mentioned above.…”
Section: Subjectsmentioning
confidence: 92%
“…Cognitive impairments (Wang, Chen, Liu, Lin & Huang, 2020) are typically associated with epileptic seizures with apparent impairment (Wang, Liu, Liu, Zhang & Wang et al, 2020) and frequent seizures (Hessen, Alfstad, Torgersen & Lossius, 2018). But not in all cases epilepsy is associated with cognitive impairments (Hermann, Loring & Wilson, 2017;Zhou, Chen, Peng & Ouyang, 2016;Galanopoulou, & Moshé, 2015).…”
Section: Introductionmentioning
confidence: 99%